Optimization of query results in peer-to-peer database supported by semantics - Valêncio, Carlos Roberto [UNESP]; Costa, Leandro Rincon [UNESP]; Carreira, Juliano Augusto [UNESP]; Tronco, Mario Luiz (Institute of Electrical and Electronics Engineers (IEEE), 2011)
The development of new technologies that use peer-to-peer networks grows every day, with the object to supply the need of sharing information, resources and services of databases around the world. Among them are the peer-to-peer databases that take advantage of peer-to-peer networks to manage distributed knowledge bases, allowing the sharing of information semantically related but syntactically heterogeneous. However, it is a challenge to ensure the efficient search for information without compromising the autonomy of each node and network flexibility, given the structural characteristics of these networks. On the other hand, some studies propose the use of ontology semantics by assigning standardized categorization of information. The main original contribution of this work is the approach of this problem with a proposal for optimization of queries supported by the Ant Colony algorithm and classification though ontologies. The results show that this strategy enables the semantic support to the searches in peer-to-peer databases, aiming to expand the results without compromising network performance. © 2011 IEEE.
Keywords: Ant colony algorithm; Distributed databases; Peer-to-peer database; Routing queries; Semantic; Ant colony algorithms; Distributed database; Distributed knowledge; Network flexibility; Ontology semantics; Peer to peer; Query results; Sharing information; Structural characteristics; Algorithms; Database systems; Network performance; Optimization; Peer to peer networks; Semantics; Distributed computer systems